PERUBAHAN STRATEGI OPERASI PENANGKAPAN IKAN NELAYAN KARIMUNJAWA, JAWA TENGAH - Eko Sri Wiyono; Tasrif Kartawijaya (Fakultas Perikanan dan Ilmu Kelautan, 2012)
Reef fishery is one of the main activities of fishermen in the tropic area. Changing of economy and ecology has resulted in changes in revenue and operating strategies of fishing. Fishermen have used a variety of strategies to maintain their activity. To examine this problem, we conducted the reseach in Karimunjawa, Central Java. The results of this study suggest that fish composition, fishing gear productivity and fishing gear which used by fishermen have changed over the period 2003 - 2005 and from 2009 to 2011. When during period of 2003 - 2005 fising trip of gear was dominated by muroami, then in the period 2009 - 2011 fishing trip dominated by speargun (arrows). These changes, thought to be caused by changes in market demand especially yellow tail (Caesio sp), the fishing operations cost and catches both in number and composition of fish.